Considerations to accelerating and maximize the preclinical studies to a safe and effective COVID-19 vaccine - Reynaldo Oliva-Hernández (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
The emergence of novel coronavirus-2019 (COVID-19) by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus and its rapid spread across the world have triggered a global health emergency without preceding. From the first report of COVID-19 at Wuhan city of China in December 2019 until today there has been an outbreak of COVID-19 around the world, with 97, 831, 595 confirmed cases and 2, 120, 877 death cases [1,2] and this number keeps growing.